Methodologies and applications of proteomics for study of yeast strains: An update - Lacerda, Maria Priscila F. [UNESP]; Marcelino, Mônica Yonashiro [UNESP]; Lourencetti, Natália M. S. [UNESP]; Neto, Álvaro Baptista [UNESP]; Gattas, Edwil A. [UNESP]; Mendes-Giannini, Maria José Soares [UNESP]; Fusco-Almeida, Ana Marisa [UNESP] (Bentham Science Publishers, 2019)
Yeasts are one of the mostly used microorganisms as models in several studies. A wide range of applications in different processes can be attributed to their intrinsic characteristics. They are eu-karyotes and therefore valuable expression hosts that require elaborate post-translational modifications. Their arsenal of proteins has become a valuable biochemical tool for the catalysis of several reactions of great value to the food (beverages), pharmaceutical and energy industries. Currently, the main challenge in systemic yeast biology is the understanding of the expression, function and regulation of the protein pool encoded by such microorganisms. In this review, we will provide an overview of the proteomic methodologies used in the analysis of yeasts. This research focuses on the advantages and improvements in their most recent applications with an understanding of the functionality of the proteins of these microorganisms, as well as an update of the advances of methodologies employed in mass spectrometry.
Keywords: Functional proteomics; Mass spectrometry; Metabolism; Protein profiling; Quantitative proteomics; Yeast